2009
DOI: 10.1186/1757-1626-2-6691
|View full text |Cite
|
Sign up to set email alerts
|

Atypical presentation of an oesophageal carcinoma with metastases to the left buttock: a case report

Abstract: IntroductionOesophageal carcinomas represent 3% of all cancers in the UK accounting for 7650 new cases per annum. Oesophageal cancer may be associated with swallowing abnormalities, localised mass pressure effects, lymphatic or distant metastatic spread.Case presentationWe report a 50-year-old man who presented with a painful, enlarging, solid, fixed lesion adjacent to the left buttock with associated dysphagia. Initial endoscopic assessment suggested severe oesophageal inflammation while the lesion in the but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Yacouba et al . showed that of 22 reported cases of ECs with unusual presentations, 6 cases presented with osteolytic lesions, 3 cases presented with cutaneous nodules, 2 cases with dyspnea, 2 cases with upper abdominal pain, and 1 case each with gluteal mass,[ 8 ] adrenal mass, thyroid mass,[ 9 ] headache with SOL, solitary jejunal mass, painful breast lump, hip pain, cervical pain, and chronic cough. [ 5 ] Of these 22 cases, 19 were metastatic ECs and only 3 cases were nonmetastatic cancer like our case.…”
Section: Discussionmentioning
confidence: 99%
“…Yacouba et al . showed that of 22 reported cases of ECs with unusual presentations, 6 cases presented with osteolytic lesions, 3 cases presented with cutaneous nodules, 2 cases with dyspnea, 2 cases with upper abdominal pain, and 1 case each with gluteal mass,[ 8 ] adrenal mass, thyroid mass,[ 9 ] headache with SOL, solitary jejunal mass, painful breast lump, hip pain, cervical pain, and chronic cough. [ 5 ] Of these 22 cases, 19 were metastatic ECs and only 3 cases were nonmetastatic cancer like our case.…”
Section: Discussionmentioning
confidence: 99%